Intraoperative Radiotherapy Is Not a Better Alternative to Whole Breast Radiotherapy as a Therapeutic Option for Early-Stage Breast Cancer - Wang, Linwei; Sun, Min; Yang, Shuailong; Chen, Yuanyuan; Li, Tian (Frontiers in Oncology, 2021)
Objective: Intraoperative radiotherapy (IORT) in early-stage breast cancer has been studied over the years. However, it has not been demonstrated whether IORT is more suitable as a therapeutic option for early-stage breast cancer than whole breast radiotherapy (WBRT). Therefore, we performed a meta-analysis to compare the efficacy and safety of IORT to those of WBRT as therapeutic options for early-stage breast cancer patients receiving breast-conserving surgery. Methods: PubMed, Embase, and Cochrane Library databases were searched from inception to October 2021. Computerized and manual search were adopted to identify eligible randomized control trials from online databases. Risk ratio (RR) and 95% confidence intervals were calculated by random-effects models to assess the relative risk. Potential publication bias was quantified by Begg’s and Egger’s tests. Results: Based on our inclusion criteria, 10 randomized control trials involving 5,698 patients were included in this meta-analysis. This meta-analysis showed that the IORT group was associated with a higher local recurrence risk (RR = 2.111, 95% CI, 1.130 - 3.943, P = 0.0191), especially in the long-term follow-up subgroup or published after 2020 subgroup or Caucasian subgroup (RR = 2.404, 95% CI, 1.183 - 4.885, P = 0.0154). Subgroup analysis showed that IORT group had a higher recurrence risk than the WBRT group in polycentric randomized controlled trial subgroup (RR = 1.213, 95% CI, 1.030 – 1.428, P = 0.0204). Pooled analysis showed that there was no statistically significant difference in overall survival, recurrence-free survival, distant metastasis-free survival and cancer-specific survival between IORT and WBRT groups. Additionally, the risk of skin toxicity was reduced, but the incidences of fat toxicity, edema and scar calcification were significantly increased in the patients who underwent IORT in comparison to those who underwent WBRT. Conclusion: This meta-analysis revealed that IORT was not a better alternative to WBRT. More large-scale and well-designed clinical trials with longer follow-up periods are encouraged to further investigate the value of IORT.